2016
DOI: 10.1016/j.msec.2016.01.091
|View full text |Cite
|
Sign up to set email alerts
|

Is cell viability always directly related to corrosion resistance of stainless steels?

Abstract: It has been frequently reported that cell viability on stainless steels is improved by increasing their corrosion resistance. The question that arises is whether human cell viability is always directly related to corrosion resistance in these biostable alloys. In this work, the microstructure and in vitro corrosion behavior of a new class of medical-grade stainless steels were correlated with adult human mesenchymal stem cell viability. The samples were produced by a powder metallurgy route, consisting of mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…Assessing the presence of corrosion and of cell necrosis after applying electricity showed that corrosion did not always lead to cell necrosis. Shalahinejad et al found that there is no direct correlation between cell viability and corrosion resistance [14]. Result from previous studies also support the results of this study.…”
Section: Discussionsupporting
confidence: 90%
“…Assessing the presence of corrosion and of cell necrosis after applying electricity showed that corrosion did not always lead to cell necrosis. Shalahinejad et al found that there is no direct correlation between cell viability and corrosion resistance [14]. Result from previous studies also support the results of this study.…”
Section: Discussionsupporting
confidence: 90%